Aflatoxin and food safety - Abbas, Hamed K. (Taylor & Francis, 2005)
Aflatoxins are responsible for damaging up to 25% of the world’s food crops, resulting in large economic losses in developed countries and human and animal disease in under-developed ones. In addition to aflatoxins, the presence of other mycotoxins, particularly fumonisins, brings additional concerns about the safety of food and field supplies. There has not been a comprehensive, single source guide to synthesize the most up-to-date information on this issue – until now.